2019
DOI: 10.1111/isj.12267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical managers' identity at the crossroad of multiple institutional logics in it innovation: The case study of a health care organization in England

Abstract: Clinical managers play a crucial role in securing the implementation and sustainability of information technology (IT) innovation in health care. Yet, not all clinical managers are willing and able to support IT innovation, particularly when the institutional logics of an IT innovation challenge their professional practice. We investigate how clinical managers use their hybrid identities to reconcile differences among competing institutional logics that affect IT innovation. Based on three examples of IT innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…Hansen and Baroody (2020) studied the adoption and use of electronic health record systems in hospitals and identified four prominent logics: medical professionalism, private sector managerialism, technical design, and regulatory oversight. Bernardi and Exworthy (2019) studied IT innovation in healthcare and found that different types of innovation have different effects on the relationship between the institutional logics of managerialism, medical professionalism, and patient‐centred care. Currie and Guah (2007) found that medical professionalism and managerial and market logics shaped the implementation of the IT programme for the national healthcare system in the United Kingdom.…”
Section: Enterprise Architecture and Healthcare As A Site Of Institutional Pluralismmentioning
confidence: 99%
See 2 more Smart Citations
“…Hansen and Baroody (2020) studied the adoption and use of electronic health record systems in hospitals and identified four prominent logics: medical professionalism, private sector managerialism, technical design, and regulatory oversight. Bernardi and Exworthy (2019) studied IT innovation in healthcare and found that different types of innovation have different effects on the relationship between the institutional logics of managerialism, medical professionalism, and patient‐centred care. Currie and Guah (2007) found that medical professionalism and managerial and market logics shaped the implementation of the IT programme for the national healthcare system in the United Kingdom.…”
Section: Enterprise Architecture and Healthcare As A Site Of Institutional Pluralismmentioning
confidence: 99%
“…Actors with different functions and professional backgrounds are assumed to invoke different logics due to the differences in their work, education, and overall socialization patterns (Boonstra et al, 2018). Nevertheless, nascent IS research has shown that multiple institutional logics can influence the behaviour of actors that have complex roles as in the case of clinical managers that deploy multiple identities and their social position to facilitate IT innovation at the crossroad of multiple institutional logics (Bernardi & Exworthy, 2019). Empirical institutional research has shown that in everyday practices, actors do not always adhere to the logics of their professional groups but may invoke a mix of logics (Martin, Currie, Weaver, Finn, & McDonald, 2017;McPherson & Sauder, 2013;Waldorff, Reay, & Goodrick, 2013).…”
Section: Sources Of Legitimacymentioning
confidence: 99%
See 1 more Smart Citation
“…In the fifth article, Bernardi and Exworthy () demonstrate how clinical managers' perception of their hybrid role in relation to their professional identity influences their response to the conflicting institutional demands of IT innovation. Based on three examples of IT innovation (telehealth for Obstructive Sleep Apnoea, telehealth for Heart Failure, and Electrocardiograms) in a healthcare organization in England, they identify three roles in IT innovation (innovation advocate, innovation broker, innovation laggard) that clinical managers enacted in response to three degrees of conflict between institutional logics (no conflict, moderate conflict, and high conflict), respectively.…”
mentioning
confidence: 99%
“…Literature to date has focused, in the main, on the investigation of professional-managerial hybrid identities. However, we give particular prominence to hybrid professional-leader identity (Bernardi et al, 2020). These two hybrid identity combinations differ in their emphasis.…”
Section: Introductionmentioning
confidence: 87%